2008
DOI: 10.1016/j.apm.2006.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Extensions of TOPSIS for large scale multi-objective non-linear programming problems with block angular structure

Abstract: This paper focuses on multi-objective large-scale non-linear programming (MOLSNLP) problems with block angular structure. We extend the technique for order preference by similarity ideal solution (TOPSIS) to solve them. Compromise (TOPSIS) control minimizes the measure of distance, provided that the closest solution should have the shortest distance from the positive ideal solution (PIS) as well as the longest distance from the negative ideal solution (NIS). As the measure of ''closeness'' L P -metric is used.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
26
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(26 citation statements)
references
References 10 publications
0
26
0
Order By: Relevance
“…After the publication of the Dantzig and Wolfe decomposition method [7], there have been numerous subsequent works on large scale linear and nonlinear programming problems with block angular structure ( [1,6,12]). Abo Sinna et al [4] extended the technique for order preference by similarity ideal solution (TOPSIS) to solve multi-objective large scale non-linear programming problem. Compromise (TOPSIS) control minimizes the measure of distance.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…After the publication of the Dantzig and Wolfe decomposition method [7], there have been numerous subsequent works on large scale linear and nonlinear programming problems with block angular structure ( [1,6,12]). Abo Sinna et al [4] extended the technique for order preference by similarity ideal solution (TOPSIS) to solve multi-objective large scale non-linear programming problem. Compromise (TOPSIS) control minimizes the measure of distance.…”
Section: Introductionmentioning
confidence: 99%
“…El-Sawy et al [9] introduced an algorithm for decomposing the parametric space in large scale linear vector optimization problems under fuzzy environment. Recently, notable studies have been done in the area of multi-level and multi-objective large scale programming problems ( [3,4,6,12]). Benzi et al [6] developed and compared multi-level algorithms for solving large scale bound constrained nonlinear problems via interior point methods.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Xu (2007) defined the notations of the positive ideal fuzzy set and negative ideal fuzzy set, which can be used in fuzzy TOPSIS or other fuzzy MADM methods. Abo-Sinna et al (2008) extended the TOPSIS for large-scale multi-objective non-linear programming problems with block angular structure. Nut and Soner (2008) proposed an integrated approach using AHP and TOPSIS in a fuzzy environment for shipping site selection.…”
Section: Introductionmentioning
confidence: 99%
“…TOPSIS method was initially proposed by Hwang and Yoon(1981) [13,14], The basic idea of the TOPSIS method is that the chosen alternative should have the shortest distance from the positive ideal solution (PIS) and the farthest distance from the negative ideal solution (NIS). As various types of uncertainties and imprecision often exist, the information of alternatives are vague, imprecise and uncertain by nature, a variety of more in-depth-study of a new approach emerged, such as those reported in Lai et al [12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%